Update on the prevalence of persistent post-traumatic headache in adult civilian traumatic brain injury: protocol for a systematic review and meta-analysis - Arbour, Caroline (BMJ Open, 2020)
INTRODUCTION: Traumatic brain injury (TBI) is a major public health concern. Persistent post-traumatic headache (PTH) is a common consequence of TBI affecting productivity and quality of life. The only review providing information about headache prevalence after TBI was published in 2008, combined data from civilian and military TBI, and was strictly derived from Medline database. Due to recent changes in TBI diagnosis and trauma epidemiology, the aim of the current study is to perform a systematic review and meta-analysis to derive updated prevalence estimates of persistent PTH in adult civilian TBI. METHODS AND ANALYSIS: The methods have been defined following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies published from 2008 to 2019 will be identified searching the electronic databases Medline, Embase, Cochrane, Google Scholar, Directory of Open Access Journals and Web of Science. Retrieved records will be independently screened by two authors and relevant data will be extracted from studies reporting data on persistent PTH prevalence among civilian TBI individuals (≥16 years). The pooled prevalence estimates of any form of headache will be computed applying random-effects meta-analysis. Heterogeneity will be assessed using the I(2) statistic and explored through subgroup analyses considering TBI severity (mild vs moderate/severe). Estimations of risk of bias will be performed using the Risk of Bias Tool for Prevalence Studies. ETHICS AND DISSEMINATION: The result of this systematic review will be published in a peer-reviewed journal and disseminated at relevant conferences presentations. Formal ethical approval is not required because we will search and evaluate only existing sources of literature. By focusing on studies conducted in the last decade, this review will provide the most up-to-date information about the global prevalence of persistent PTH after TBI. Considering the economical and social burden of persistent PTH after TBI, accurate estimates of this problematic disorder is of utmost importance for planning, implementing and evaluating prevention interventions. PROSPERO REGISTRATION NUMBER: CRD42018094138